2018
DOI: 10.1016/j.jid.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of G-Quadruplex–Forming Oligonucleotide Homologous to the Telomere Overhang in Melanoma

Abstract: T-oligo, a guanine-rich oligonucleotide homologous to the 3'-telomeric overhang of telomeres, elicits potent DNA-damage responses in melanoma cells; however, its mechanism of action is largely unknown. Guanine-rich oligonucleotides can form G-quadruplexes (G4), which are stabilized by the hydrogen bonding of guanine residues. In this study, we confirmed the G4-forming capabilities of T-oligo using nondenaturing PAGE, nuclear magnetic resonance, and immunofluorescence. Using an anti-G-quadruplex antibody, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…CRC cells (2 × 10 3 ) were grown overnight on a Lab-Tek®II CC2 Chamber slideTM System (Cat#154917, Nunc, Rochester, NY, USA) as described previously [16,62]. Cells were fixed with chilled methanol for 10 minutes and washed with PBS.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…CRC cells (2 × 10 3 ) were grown overnight on a Lab-Tek®II CC2 Chamber slideTM System (Cat#154917, Nunc, Rochester, NY, USA) as described previously [16,62]. Cells were fixed with chilled methanol for 10 minutes and washed with PBS.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…4 The most frequently found pathogen is Staphylococcus aureus (S. aureus), infecting 44-76% of CTCL patients. 5,6 In a murine CTCL disease model, it has been shown that bacterial infections aggravate the disease 7 and a reduction of colonizing bacteria in CTCL patients with antibiotics has been associated with clinical improvement and a decrease in tumour burden. 8,9 This suggests that S. aureus and its toxins fuel disease progression (as reviewed in 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…T‐oligo has shown anticancer activity in multiple cancer cell lines in vitro . In a pancreatic cancer cells experiment, cell viability decreased to 26% within a 48‐hour period after treatment with T‐oligo .…”
Section: Oligonucleotides Targeting Telomeres and Telomerasementioning
confidence: 99%